Relationship Between Posttraumatic Stress Symptoms and Cardiovascular Disease Risk in Firefighters. Issue 2 (March 2022) - Angleman, Amy J.; Van Hasselt, Vincent B.; Schuhmann, Bailee B.
The impact of occupational stress on first responders has received increased investigative attention in recent years. However, research specifically targeting firefighters and their unique responses to job related stress remains limited. Although cardiovascular disease (CVD) risk has been recognized in firefighters, behavioral and psychological contributions (e.g., posttraumatic stress) have not been adequately examined. The purpose of this study was to: (1) examine the relationship between posttraumatic stress symptoms and CVD risk in firefighters, (2) assess the effects of service time on the relationship, and (3) increase understanding of the manifestations of stress in this population. Participants were 87 firefighters from Special Operations teams. Self-report measures of posttraumatic stress symptoms, health, and length of service were administered. Data from annual physical examinations provided information regarding CVD risk (weight, height, blood pressure, cholesterol, smoking, physical exercise). Results indicated significant relationships between posttraumatic stress symptomatology and current smoking status, triglyceride levels, and the number of CVD risk factors. Findings suggest that the presence of posttraumatic stress symptoms may influence overall CVD risk and may not be moderated by years of fire service. Implications for behavioral interventions with firefighters are discussed. Suggestions for future research in this area are offered.